EUS in Pediatrics: A Multicenter Experience and Review - Piester, Travis L.; Liu, Quin Y. (Frontiers in Pediatrics, 2021)
Background/Aim: Endoscopic ultrasound (EUS) is a well-established tool used in the evaluation and treatment of a wide range of pathology in adult medicine. EUS in pediatrics has been shown to be safe and technically effective, and its use continues to evolve. This article aims to describe the EUS experience at our tertiary care centers with regards to safety, technical success, and its impact in clinical management. We also discuss the current and developing diagnostic and therapeutic uses for EUS in pediatrics such as in pancreaticobiliary disease, congenital anomalies, eosinophilic esophagitis, inflammatory bowel disease, and liver disease. Methods: This is a retrospective review of EUS performed by two Pediatric Gastroenterologist trained endosonographers between April 2017 through November 2020. Patient demographics, procedure indication, procedure characteristics, technical success, and complications were collected. Literature review was performed to describe current and future uses of EUS in pediatrics. Results: 98 EUS were performed with 15 (15.3%) including fine needle aspiration/biopsy and 9 (9.2%) cases being therapeutic. Most common indications include choledocholithiasis (n = 31, 31.6%), pancreatic fluid collections (n = 18, 18.4%), chronic and acute recurrent pancreatitis (n = 14, 14.3%), and acute pancreatitis characterization (n=13, 13.3%). Notable indications of pancreatic mass (n=6, 6.1%) and luminal lesions/strictures (n=6, 6.1%) were less common. Complications were limited with 1 instance of questionable GI bleeding after cystgastrostomy creation. 98/98 (100%) of cases were technically successful. Conclusion/Discussion: EUS has been shown to be performed safely and successfully in the pediatric population by pediatric endosonographers. This study and review support its use in pediatric practice and demonstrates the wide variety of indications for EUS such as pancreatic cystgastrostomy, celiac plexus neurolysis and evaluation of chronic pancreatitis. This literature review also demonstrates areas of potential development for EUS within the practice of pediatric gastroenterology.